Nilai-Nilai Humanis dalam Film 8 Rue de l’Humanité Karya Dany Boon - Prameswari, Pradnya Paramitha; Lustyantie, Ninuk Lustyantie; Dewi, Evi Rosyani Dewi (Program Studi Pendidikan Bahasa Prancis FBS UNJ, 2024)
This research aims to describe the elements of humanist values contained in the movie 8 Rue de l’Humanité by Dany Boon. The main source used as the basis of this research is Peterson and Seligman’s theory of humanist value which consist of three elements of humanist value, such as love, kindness, and social intelligence. This research uses a qualitative approach with a content analysis method and structural theory of literary to determine the intrinsic elements in the movie, such as plot, sequence, character, and setting. In this research, the data used are words, phrases, and sentences that contain elements of humanist values with the data source being the movie 8 Rue de l’Humanité by Dany Boon. The data analysis technique in this research refers to the Miles, Huberman, and Saldaña model, consisting of data condensation, data display, and data conclusion drawing /verification. The results of this research show that there are 35 data indicating the existence of elements of humanist value in the movie 8 Rue de l’Humanité by Dany Boon. The most element of humanist value found is kindness with 17 (seventeen) data. Then, love with 9 (nine) data, and social intelligence with 9 (nine) data.